An Analysis of the Challenges of Implementing Islamic Finance to Support a Green Economy: Evidence from Siak Regency - Jum Harroni; Muhammad Habibi Siregar; Muhammad Irwan Padli Nasution (Journal of Islamic Economic and Business Research, 2026)
This study aims to analyze the challenges of implementing Islamic finance to support green economy development in Siak Regency, Indonesia, and identify the strategic factors that hinder or enable its effective contribution to sustainable development. The study employs a qualitative case study approach using primary data collected through in-depth interviews with 12 participants, including Islamic financial institution practitioners, local government, green economy business actors, and academics. Secondary data were obtained from policy documents, institutional reports, and relevant literature. Data were analyzed using Reflexive Thematic Analysis (RTA) based on the conceptual framework of maqasid al-shariah, Islamic financial instruments, Environmental, Social, and Governance (ESG) principles, and green economy development. The findings reveal that Islamic finance remains in its early stages of supporting the green economy and has not yet fully translated the maqasid al-shariah values into operational sustainability practices. Five major challenges were identified: regulatory and policy barriers, limited Islamic green finance literacy, weak ESG integration, technological constraints, and stakeholder collaboration challenges. These factors collectively limit the contribution of Islamic finance to green economic transformation. The study implies that strengthening regulatory coherence, ESG operationalization, digital innovation, public literacy, and multi-stakeholder collaboration is essential to enhance the effectiveness of Islamic finance in promoting sustainable development. The novelty of this research lies in its integrated analysis of Islamic finance, ESG, and green economy implementation at the regional level, while proposing an operational framework that combines maqasid al-shariah, sustainability principles, and stakeholder collaboration to support green economic development.